Verification of an Accommodative Response for Depth Measurement of Floating Hologram Using a Holographic Optical Element - Leehwan Hwang; Sungjae Ha; Philippe Gentet; Jaehyun Lee; Soonchul Kwon; Seunghyun Lee (Applied Sciences, 2020)
Floating holograms using holographic optical element screens differ from existing systems because they can float 2D images in the air and provide a sense of depth. Until now, the verification of such displays has been conducted only on the system implementation, and only the diffraction efficiency and angle of view of the hologram have been verified. Although such displays can be directly observed with the human eye, the eye’s control ability has not been quantitatively verified. In this study, we verified that the focus of the observer coincided with the appropriate depth value determined with experiments. This was achieved by measuring the amount of control reaction from the perspective of the observer on the image of the floating hologram using a holographic optical element (HOE). An autorefractor was used, and we confirmed that an image with a sense of depth can be observed from the interaction of the observer’s focus and convergence on the 2D floating image using a HOE. Thus, the realization of content with a sense of depth of 2D projected images using a HOE in terms of human factors was quantitatively verified.